Ambang Batas Pengelolaan Alam: Ayat-Ayat Lingkungan Tentang Keseimbangan Pemanfaatan - Mirwan Sudarmawan Rifai; Rahmi Damis; Hasyim Hadade (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the Qur’anic concept of balance in the utilization of natural resources and to formulate the ethical limits of natural resource exploitation through a thematic Qur’anic exegesis (tafsir maudhu‘i) approach. The research is motivated by the growing global ecological crisis, which is largely driven by excessive exploitation of natural resources and has resulted in widespread environmental degradation, including deforestation, flooding, landslides, and climate change. Employing a library research method, this study analyzes relevant Qur’anic verses concerning the environment by drawing upon classical and contemporary Qur’anic commentaries, as well as other pertinent scholarly literature. The data are examined using a descriptive-analytical approach to explore the relationship between the Qur’anic texts and the interpretations of Muslim exegetes regarding the principles of ecological balance, human stewardship (khil?fah), and the prohibition of environmental destruction. The findings reveal that the Qur’an views nature as a divine trust (am?nah) that must be managed responsibly, equitably, and sustainably. The principles of moderation, balance, environmental stewardship, and the prohibition of corruption on earth constitute the normative foundation for Islamic environmental ethics. This study concludes that the exploitation of natural resources should be governed by the principles of public welfare (ma?la?ah), ecological balance, and environmental responsibility, thereby positioning the Qur’anic eco-theological perspective as a fundamental framework for promoting sustainable development.